2013
DOI: 10.1111/apt.12307
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive tests for fibrosis and liver stiffness predict 5‐year survival of patients chronically infected with hepatitis B virus

Abstract: SUMMARY BackgroundLiver stiffness and non-invasive tests predict overall survival in chronic hepatitis C. However, in patients chronically infected with hepatitis B virus (HBV), only the association between liver stiffness and the risk of hepatocellular carcinoma has been published.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 45 publications
5
68
1
3
Order By: Relevance
“…[33] TE (part of a score) ---0.83-0.89 Elastography to predict the liver related death of the patients with liver cirrhosis Rate of death Pang et al [38] TE 40 kPa 34%/3 yr de Lédinghen et al [39] TE < 9 kPa 2.9%/5 yr > 20 kPa 38.5%/5 yr TE: Transient elastography (fibroscan); ARFI: Acoustic radiation force impulse imaging.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[33] TE (part of a score) ---0.83-0.89 Elastography to predict the liver related death of the patients with liver cirrhosis Rate of death Pang et al [38] TE 40 kPa 34%/3 yr de Lédinghen et al [39] TE < 9 kPa 2.9%/5 yr > 20 kPa 38.5%/5 yr TE: Transient elastography (fibroscan); ARFI: Acoustic radiation force impulse imaging.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown by many studies that measuring liver elasticity one can predict the survival of a patient [37][38][39][40] . In the study conducted by Wong et al [37] , they found age, Hui index and liver stiffness to be independent predictors of hepatic event -free survival.…”
Section: Liver Elastography In the Prediction Of The Survival Of The mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a number of noninvasive tests of liver fibrosis have been developed and validated against liver histology [33,34]. They are noninferior to liver histology in predicting future HCC development and mortality [35,36]. As a result, current European and Latin American guidelines endorse the use of transient elastography and serum tests as initial assessment of liver fibrosis in patients with chronic hepatitis B [37].…”
Section: Hbeag: a Test Through Historymentioning
confidence: 99%
“…A limitation of all the studies performed thus far is that the reference shear wave TE values for each fibrosis stage were calculated from their own cohort of patients after data collection, and these differ across studies (Shaheen et al, 2007;de Ledinghen and Vergniol, 2008;Stebbing et al, 2010;Tsochatzis et al, 2011). The studies mainly focused on chronic hepatitis C/B, with special emphasis on chronic hepatitis C patients (Ziol et al, 2005;Rigamonti et al, 2008;Lemoine et al, 2008;Chen et al, 2012;de Lédinghen et al, 2013;Feier et al, 2013;Calvaruso et al, 2013). The shear wave values of 7, 9.5, and 12 kPa corresponding to stages F2, F3, and F4, respectively, were used.…”
Section: Introductionmentioning
confidence: 99%